Crimes and the extraction without future: the case of the rubber exploitation in Putumayo (1880-1915) - Salazar Paiva, Jesús Franco (2019)
Was rubber exploitation really seen as an opportunity for Peruvian development at the end of the 19th century and at the beginning of the 20th century? In the present essay, it is considered that there was a perception of lost opportunity both in the social and in the economic plane. In the first place, this economic activity was overshadowed by the reports of atrocious crimes against the indigenous population in Putumayo. The seriousness of the abuses put into the public debate a reflection on a human sense of civilization, as opposed to a manipulation of the theories of social Darwinism that were used to defend the indefensible. Secondly, the depredation of resources and the absence of a vision of the future were other variables that at the time were perceived as defects to establish true development. This two dimensions shapes of the sensation of lost opportunity.